Pengaruh Permainan Eksplorasi Bermain Air Terhadap Perkembangan Sosial Emosional Anak Usia Dini - Siti Marli’ah (Program Studi PGRA, 2016)
This research aims to test the effects of exploration play to child’s social emotional development. Experimental quantitative approach in this research uses nonequivalent control group design. This research was conducted to 40 children from Amanah Islamic kindergarten and 37 children from Al Fajar Islamic kindergarten. Data of research is collected by observationand documentation techniques using social emotional developments observation guides. In this research, data analysis is conducted by means of SPSS 20.0 for Windows Evaluation Version using MANOVA test. The results showed the value of F calculated at 8.950 with a significant level (sig 0.004 < 0.05), so that the hypothesis can be accepted. Base on the research result, it can be summarized that exploratory play has effect to child’s social emotional development